2022
DOI: 10.3390/ijms24010278
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Expression Profile of Myricetin-Treated THP-1 Macrophages Exhibits Alterations in Atherosclerosis-Related Regulator Molecules and LXR/RXR Pathway

Abstract: Atherosclerosis is a chronic inflammation characterized by macrophage infiltration, lipid deposition, and arterial wall thickening. Prevention of atherosclerosis by nutraceuticals is gaining attention. Myricetin, a dietary flavonol, is claimed to possess anti-atherosclerosis properties. We studied myricetin’s effect on the atherosclerosis-associated molecular mechanism. Cytotoxicity and proliferation testing to check the viability of myricetin-treated THP-1 macrophages and monocyte migration study in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Moreover, studies examining bioactive substances indicated that they considerably inhibited SR-AI or CD36 expression, even though they didn't use modified LDL as a positive control to verify their findings [37,38]. On the other hand, quercetin and myricetin have been shown in RT-qPCR and microarraybased studies to have anti-atherogenic properties in THP-1 macrophages despite their increased expression of SR-AI and CD36 at the gene level [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies examining bioactive substances indicated that they considerably inhibited SR-AI or CD36 expression, even though they didn't use modified LDL as a positive control to verify their findings [37,38]. On the other hand, quercetin and myricetin have been shown in RT-qPCR and microarraybased studies to have anti-atherogenic properties in THP-1 macrophages despite their increased expression of SR-AI and CD36 at the gene level [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Myricetin (3,3 0 ,4 0 ,5,5 0 ,7-hexahydroxyflavone) is a dietary flavonol without toxicity (Huwait et al, 2023). The compound exhibits many activities, including strong antioxidant, antineoplastic, antihyperlipidaemic, and antiinflammatory (Singh and Bast, 2015;Semwal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%